An Update on the Known Host Range of the Brazilian Vaccinia Virus: An Outbreak in Buffalo Calves - Lima, Mauricio Teixeira; Oliveira, Graziele Pereira; Afonso, José Augusto Bastos; Souto, Rodolfo José Cavancanti; de Mendonça, Carla Lopes; Dantas, Antonio Flavio Medeiros; Abrahao, Jonatas Santos; Kroon, Erna Geessien (Frontiers in Microbiology, 2019)
Even after almost forty years since the eradication of smallpox, members of Poxviridae family continue to be the target of an increasing number of studies. Among these studies, prominently stands vaccinia virus, an orthopoxvirus that is associated with bovine vaccinia outbreaks. Although more frequently associated with infections in cattle and humans, host range of vaccinia virus is not restricted only to these hosts. There are several molecular and serological evidences of circulation vaccinia virus among wildlife species. In addition, viral isolation has confirmed a broad spectrum of vaccinia virus hosts. In this report, we provide a brief update on the host range of Brazilian vaccinia virus, and present a case description of an outbreak in domestic buffalo calves from Northeastern Brazil that corroborates previous serological and molecular studies. Furthermore, in the present study, the vaccinia virus has been isolated for the first time in buffaloes, and referred to as vaccinia virus Pernambuco (VACV-PE). Phylogenetic reconstruction based on A56R clustered VACV-PE with vaccinia virus isolates belonging to group 1 Brazilian vaccinia virus. Furthermore, the vaccinia virus genome was detected in the milk of a lactating cow, which thereby revealed a pathway for future studies on the possible impact of vaccinia virus on buffalo milk and milk products. Taken together, these results provide the first description of clinical disease caused by vaccinia virus in buffaloes in South America, and they raise new questions about the chain of transmission of this virus.